Síntese, caracterização e aplicação adsortiva de um novo agente sililante imobilizado na sílica gel por rotas distintas - Pinto, Victor Hugo e Araujo (2009)
The reaction between 3-aminopropyltriethoxysilane (AMPTS) with thioglycolic acid (TGA) resulted in a new sililante agent, AMPTGA. This matrix has nitrogen, oxygen and sulfur as basic centers, that have ability to adsorb metallic cations in solution. Immobilization of AMPTGA onto silica gel surface was developed by using conventional heterogeneous method, using toluene as solvent under reflux and stirred in an inert atmosphere at 100 °C. Another method was adopted in accordance with the principles of green chemistry, which water was used as solvent and at room temperature. The new solids were characterized by elemental analysis of CHNS, infrared spectroscopy, NMR 13C and 29Si, thermogravimetric analysis, surface area, and SEM (only AMPTGA). The reaction route using water, as solvent did not reach the desired immobilization. Moreover, the conventional approach to heterogeneous reaction was effective, the compound was called Sil-NTGA. The elemental analysis indicated the possible structures formed in agreement with the molar ratio C / N 3:1 for Sil-AMPTGA, 4:1 for Sil-NH2 and 5:1 for Sil-NTGA. The surface area were 429, 384, 193 and 0.43 m2g-1 for solids Sil-NH2, Sil-NTGA, Sil-AMPTGA and AMPTGA, respectively, which were lower than that of silica gel precursor 484 m2g-1. In all solid reported, the infrared spectra regions showed bands at 3400, 2930, 1100 cm-1 features to OH, -CH and Si-O-Si- stretch vibrations, respectively. For Sil-NTGA we also observed a band at 2520 cm-1 related to the group-SH stretch vibration. The NMR spectra signals of 13C and 29Si corroborate with the other results. Matrices, AMPTGA, Sil-AMPTGA and Sil-NTGA were applied to adsorption of divalent copper, nickel and cobalt in aqueous solution. The process of metal extraction was followed by the batch method and the maximum extraction (nf) found for each surface was: on the surface Sil-AMPTGA were 2.26, 1.50 and 0.89 mmol g-1 for Cu2+, Ni2+ and Co2+, respectively. On matrix AMPTGA, were 1.66, 1.34 and 1.33 mmol g-1 for Ni2+, Co2+ and Cu2+, respectively. While for Sil-NTGA, nf data were 1.84 mmol g-1, 1.18 mmol g-1 and 1.02 mmol g-1 for Cu2+, Ni2+ and Co2+, respectively. The isotherms of Sil-NTGA influenced by the ionic strength of the medium and pH variation showed that the coverage of cations increases with increasing pH and decreases with increasing ionic strength for all pH values.